Effects of blood flow restriction training on bone turnover markers, microstructure, and biomechanics in rats - Song, Yawei; Wang, Hao; Chen, Liang; Shangguan, Yuwen; Jia, Hu (Frontiers in Endocrinology, 2023)
Objective: This study aimed to investigate the effects of blood flow restriction training on muscle strength, bone tissue structure material, and biomechanical properties in rats applying various exercise interventions and to analyze the process by identifying the bone turnover marker. Methods: A total of 24 male SD rats were randomly divided into CON group, LIRT group , HIRT group , and LIBFR group for 8week ladder climbing exercises. The LIRT group was allowed to climb the ladder with 30% of the MVCC. The HIRT group were allowed to climb the ladder with 70% MVCC. The LIBFR group climbed the ladder with 30% MVCC while imposing blood flow restriction. The PINP, BGP, and CTX in the serum were measured using ELISA. The bone mineral density and microstructure were measured using micro-CT. Three-point bending and torsion tests were performed by a universal testing machine to measure the material mechanics and structural mechanics indexes. Results: The MVCC in LIRT, HIRT, and LIBFR groups was significantly greater than in the CON group, while the MVCC in the HIRT group was significantly higher than that in the LIRT group (P<0.05). The PINP and BGP were significantly lower in the CON group than in the HIRT group (P<0.01), while those were significantly higher in the LIRT group compared to the HIRT group (P<0.01). The HIRT and other groups show that significant differences. (P<0.05). The HIRT group had significantly greater bone density index values than the CON and LIRT groups (P<0.05). The elastic modulus and maximum load indexes of the HIRT group were significantly smaller than those of the LIBFR group (P<0.05). The fracture load indexes in the HIRT group were significantly smaller than in the LIBFR group (P<0.05). Conclusions 1. LIRT, HIRT, LIBFR, and CON all have significant differences, and this training helps to improve maximum strength, with HIRT being the most effective. 2. Blood flow restriction training can improve the expression of the PINP and BGP. 3. Blood flow restriction training can improve muscle strength and increase the positive development of bone turnover markers, thereby improving bone elastic modulus and maximum load.